Optimalisasi Manajemen Reproduksi Ternak Sapi melalui Penyuluhan pada Kelompok Peternak “Tunas maju” di Desa Setanggor Kecamatan Praya Barat - Aminurrahman; Ryan Aryadin Putra; Khairil Anwar; Rezki Amalyadi; Ine Karni; Ica Ayu Wandira; M. Ridwan Saedi; Zaid Al Gifari; I Gede Nano Septian; Azhary Noersidiq; Vebera Maslami; Fahrullah; Luluk Lailatun Nurjanah; Ikhwan Firhamsah (Universitas Mataram, 2026)
This community service activity aimed to improve farmers’ knowledge and skills in implementing cattle reproductive management through extension and mentoring programs. The activity was conducted with the “Tunas Maju” farmer group in Setanggor Village, Praya Barat District. The methods included preparation, material delivery, interactive discussions, and evaluation using pre-test and post-test assessments. The extension materials covered basic reproductive concepts, estrus detection, mating management, and the application of artificial insemination. The results showed an increase in farmers’ understanding, particularly in identifying estrus signs, determining the appropriate mating time, and recognizing the importance of reproductive recording. The program also enhanced farmer participation and their ability to manage reproductive practices more effectively. With improved farmer capacity, it is expected that reproductive efficiency and cattle productivity can be sustainably increased.